2017
DOI: 10.1097/igc.0000000000001088
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Low Survival Among Women With a Diagnosis of Invasive Cervical Cancer in Ghana

Abstract: In conclusion, cervical cancer survival is low in Ghana and is likely to be improved if a greater proportion of the disease is detected early. Improving knowledge of the disease for early diagnosis, reducing financial barriers, and greater organization of health care delivery are likely to improve survival from cervical cancer in Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…The chances of a cervical cancer patient to survive one year after diagnosis is 62%; three years after diagnosis, 29%; and 5 years after diagnosis, 30%. 10 Studies showed that several factors significantly correlate with cervical cancer. These are early sexual intercourse (engaged before 20 years), parity (more than three live births), and the use of hormonal contraceptives (exceeding five years).…”
Section: Introductionmentioning
confidence: 99%
“…The chances of a cervical cancer patient to survive one year after diagnosis is 62%; three years after diagnosis, 29%; and 5 years after diagnosis, 30%. 10 Studies showed that several factors significantly correlate with cervical cancer. These are early sexual intercourse (engaged before 20 years), parity (more than three live births), and the use of hormonal contraceptives (exceeding five years).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 At three years from diagnosis, overall disease-specific survival was 39%. 5 Stage at presentation (Hazard ratio (HR) for stage IV compared with stage I was 7.8; 95% CI: 4.1-14.8) and histological type (HR for other histological types compared with squamous cell carcinoma was 1.4; 95% CI: 0.4-5.9, not statistically significant) were strong predictors of cervical cancer survival. Some forms of treatment were also associated with better survival than others.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5 Structured telephone interviews were also conducted for patients and relatives to gather further information on the outcome of the disease. The second study assessed the risk factors for cervical cancer in Ghana, using a hospital-based case-control study.…”
Section: Introductionmentioning
confidence: 99%
“…In LMICs lacking well-resourced treatment centers with geographic and financial barriers, treatment outcomes have been less than desired. 3 …”
Section: Introductionmentioning
confidence: 99%